PARP inhibition is a modulator of anti-tumor immune response in BRCA-deficient tumors. (31st December 2022) - Staniszewska, Anna D.; Armenia, Joshua; King, Matthew; Michaloglou, Chrysiis; Reddy, Avinash; Singh, Maneesh; San Martin, Maryann; Prickett, Laura; Wilson, Zena; Proia, Theresa; Russell, Deanna; Thomas, Morgan; et al.
ABSTRACT: PARP inhibitors are synthetically lethal with BRCA1/2 mutations, and in this setting, accumulation of DNA damage leads to cell death. Because increased DNA damage and subsequent immune activation can prime an anti-tumor immune response, we studied the impact of olaparib ± immune checkpoint blockade (ICB) on anti-tumor activity and the immune microenvironment. Concurrent combination of olaparib, at clinically relevant exposures, with ICB gave durable and deeper anti-tumor activity in the Brca1m BR5 model vs. monotherapies. Olaparib and combination treatment modulated the immune microenvironment, including increases in CD8+ T cells and NK cells, and upregulation of immune pathways, including type I IFN and STING signaling. Olaparib also induced a dose-dependent upregulation of immune pathways, including JAK/STAT, STING and type I IFN, in the tumor cell compartment of a BRCA1m (HBCx-10) but not a BRCA WT (HBCx-9) breast PDX model. In vitro, olaparib induced BRCAm tumor cell–specific dendritic cell transactivation. Relevance to human disease was assessed using patient samples from the MEDIOLA (NCT02734004) trial, which showed increased type I IFN, STING, and JAK/STAT pathway expression following olaparib treatment, in line with preclinical findings. These data together provide evidence for a mechanism and schedule underpinning potential benefit of ICB combination with olaparib.